La digitalizzazione dei serbatoi di stoccaggio idrocarburi: la soluzione ottimale per un'analisi premanutentiva più mirata, efficiente e sicura - Salvucci, Maria Giulia (GEOmedia, 2019)
The adoption of digital processes such as BIM, has its goal in the reduction of errors in the design phase, as well as the possibility of verifying artefacts during construction. The use of 3D point clouds is becoming a key tool of BIM design; adopting a georeferenced point cloud well filtered by the "noise" generated by the surrounding environment, allows us to extrapolate a series of qualitative and quantitative information on the raw data of the survey. The case study of the TK 62 tank of the API Refinery of Falconara Marittima (AN) digitized with 3D scanning and modelling techniques open the way to new solutions for more targeted and effective maintenance and constant monitoring of hydrocarbon storage facilities.